Assessment Of Food And Nutrient Intake Of Punjabi Farm Women In The Context Of Iron Deficiency Anemia (Applied Biological Research, 2014)
Sixty non-pregnant and non-lactating adult women in the age group of  25-35 years from the farm families (land holdings between 2-4 ha) were  purposively selected from village Ayali Kalan, district Ludhiana, Punjab (India) to assess their food and nutrient intake in the context of iron  deficiency anemia. Forty percent of the subjects had their hemoglobin  tested and only 3% reported deworming treatment in the last one year.  The mean hemoglobin was 10.5 ± 1.18 g dL-1. Eighty three percent of  the subjects were anemic out of which 13 and 70% were mildly and  moderately anemic. The overall adequacy of cereals, pulses, green leafy  vegetables, roots and tubers, fruits, other vegetables, milk and milk  products, sugars and fats & oils in the diets of farm women was 98, 54,  5, 63, 49, 16, 122, 141 and 216%, respectively. Of the 7 nutrients studied,  calcium was found adequate while energy, protein, folate, ascorbic acid  and iron were marginally adequate with nutrient adequacy ratios of 75- 100%. Only β-carotene was marginally inadequate. The mean adequacy  ratio was 83% which gives satisfactory picture of nutritional intake of  the farm women. Though the intake of most of the nutrients related to  iron nutriture of farm women were marginally adequate, the  hematological profile, as revealed by the hemoglobin levels in subjects, showed dismal condition of their iron status.
Keywords: Farm women; food intake; hemoglobin; iron deficiency anemia; nutrient intake